Tooth fragments embedded in the lower lip following trauma - (:unkn) unknown (MARMARA UNIV, FAC MEDICINE, 2015)
Maxillofacial trauma and accompanying oral injury may cause dental fragments embedded in surrounding soft tissues and these fragments may go unnoticed if not properly examined. This case report describes a patient who presented to the emergency department, consulted to our department for swelling and tenderness in his lower lip and diagnosed with fragments of maxillary incisor tooth located in the lower lip. Risk factors for dental trauma, importance of initial clinical examination and management of such dental injuries in the emergency department are discussed.
Keywords: Tooth fragments; Lower lip; Trauma